2014
DOI: 10.1038/ncomms6087
|View full text |Cite
|
Sign up to set email alerts
|

Combining high-throughput phenotyping and genome-wide association studies to reveal natural genetic variation in rice

Abstract: Even as the study of plant genomics rapidly develops through the use of high-throughput sequencing techniques, traditional plant phenotyping lags far behind. Here we develop a high-throughput rice phenotyping facility (HRPF) to monitor 13 traditional agronomic traits and 2 newly defined traits during the rice growth period. Using genome-wide association studies (GWAS) of the 15 traits, we identify 141 associated loci, 25 of which contain known genes such as the Green Revolution semi-dwarf gene, SD1. Based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
407
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 472 publications
(428 citation statements)
references
References 39 publications
8
407
0
4
Order By: Relevance
“…Begum et al [36] identified seven, 10 and 11 QTL for GW, GL and GLWR, respectively, using advanced lines from IRRI's irrigated breeding program genotyped with 71,710 SNP generated by Genotyping-by-sequencing (GBS). Similarly, using 533 O. sativa landrace and elite accessions genotyped with 4,358,600 SNP derived from GBS, Yang et al [37] identified 10, 11, 19 and 21 QTL for GLWR, TGW, GW and GL, respectively. These studies clearly demonstrated that GWAS offers higher resolution for QTL mapping and can be used as a powerful complementary strategy to the classical linkage mapping using bi-parental segregation populations.…”
Section: Introductionmentioning
confidence: 99%
“…Begum et al [36] identified seven, 10 and 11 QTL for GW, GL and GLWR, respectively, using advanced lines from IRRI's irrigated breeding program genotyped with 71,710 SNP generated by Genotyping-by-sequencing (GBS). Similarly, using 533 O. sativa landrace and elite accessions genotyped with 4,358,600 SNP derived from GBS, Yang et al [37] identified 10, 11, 19 and 21 QTL for GLWR, TGW, GW and GL, respectively. These studies clearly demonstrated that GWAS offers higher resolution for QTL mapping and can be used as a powerful complementary strategy to the classical linkage mapping using bi-parental segregation populations.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput noninvasive phenotyping also has been adopted successfully to assess the genetics of estimated biomass dynamics in maize (Junker et al, 2015;Muraya et al, 2017). In a previous work, a rice automatic phenotyping platform (RAP) was designed to achieve high-throughput screening of rice (Oryza sativa) plants for genetic studies (Yang et al, 2014). In this study, the RAP was expanded for high-throughput phenotyping of maize plants.…”
mentioning
confidence: 99%
“…Genotying 199 individu F1 populasi persilangan interspesifik E guineesis x E. Oleifera dapat diselesaikan hanya dalam waktu tiga bulan dan menghasilkan peta genetik dengan kandungan marka molekuler yang padat dibanding peta genetik kelapa sawit sebelumnya berdasarkan marka AFLP dan SSR (Barcelos et al, 2002;Singh et al, 2009;Billotte et al, 2010;Ting et al, 2013). SNP chip tersebut memfasilitasi percepatan pelabelan gen-gen unggul dan aplikasinya pada pemuliaan yang pada akhirnya mempersingkat siklus pemuliaan tanaman kelapa sawit (Yang et al, 2014 …”
Section: Kemajuan Dan Potensi Aplikasiunclassified